Sex Differences in Subclinical Coronary Atherosclerotic Plaque Among Individuals With HIV on Antiretroviral Therapy. (1st August 2018) - Foldyna, Borek; Fourman, Lindsay T.; Lu, Michael T.; Mueller, Martin E.; Szilveszter, Balint; Neilan, Tomas G.; Ho, Jennifer E.; Burdo, Tricia H.; Lau, Emily S.; Stone, Lauren A.; Toribio, Mabel; Srinivasa, Suman; et al.
Abstract : Background: In high-resource settings, the HIV-attributable risk of myocardial infarction (MI) is higher among women than among men. The extent to which unique mechanisms contribute to MI risk among women vs. men with HIV remains unclear. Methods: Subclinical coronary atherosclerotic plaque characteristics—including high-risk morphology plaque features—were compared among 48 HIV-infected women [48 (41, 54) years] and 97 HIV-infected men [48 (42, 52) years] on stable antiretroviral therapy (ART) without known cardiovascular disease. These individuals had previously completed coronary computed tomography angiography and metabolic/immune phenotyping as part of a prospective study. Results: Extending previous analyses, now focusing exclusively on ART-treated participants, we found that HIV-infected women had a lower prevalence of any subclinical coronary atherosclerotic plaque (35% vs. 62%, P = 0.003) and a lower number of segments with plaque ( P = 0.01), compared with HIV-infected men. We also report for the first time that ART-treated HIV-infected women had a lower prevalence of high-risk positively remodeled plaque (25% vs. 51%, P = 0.003) and a lower number of positively remodeled plaque segments ( P = 0.002). In models adjusting for cardiovascular risk factors, we further showed that male sex remained associated with any coronary plaque [odds ratio 3.8, 95% confidence interval: (1.4 to 11.4)] and with positively remodeled plaque [odds ratio 3.7, 95% confidence interval: (1.4, 10.9)]. Conclusions: ART-treated HIV-infected women (vs. HIV-infected men) had a lower prevalence and burden of subclinical coronary plaque and high-risk morphology plaque. Thus, unique sex-specific mechanisms beyond subclinical plaque may drive the higher HIV-attributable risk of MI among women vs. men. Abstract : Supplemental Digital Content is Available in the Text.